2023
DOI: 10.3390/ani13050931
|View full text |Cite
|
Sign up to set email alerts
|

A One-Year Retrospective Analysis of Viral and Parasitological Agents in Wildlife Animals Admitted to a First Aid Hospital

Abstract: This study aimed to provide information on the presence and frequency of viral and parasitic agents in wildlife presented to a Veterinary Teaching Hospital in 2020–2021. Serum and faecal samples were collected from 50 rescued animals (roe deer, fallow deer, foxes, badgers, pine martens, and porcupines) and examined by serological, molecular, and parasitological techniques. Transtracheal wash (TTW) was also collected post-mortem from roe deer. Overall, the results of the different techniques showed infections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…Metagenomics studies performed on rodents in China and red foxes in the Netherlands revealed novel rodent and fox astroviruses, respectively [ 31 , 32 ]. In our study, we screened a broad range of animal species using the method Chu et al [ 19 ] successfully applied for the detection of astroviruses in bats in Poland [ 18 ], in wild boars in Slovakia [ 29 ], and in different wild animals in Italy [ 33 ]. Although astroviruses were most frequently detected in rat samples, with a prevalence of 33.3%, the number of samples tested was only nine due to the low number of rat samples submitted during rabies surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomics studies performed on rodents in China and red foxes in the Netherlands revealed novel rodent and fox astroviruses, respectively [ 31 , 32 ]. In our study, we screened a broad range of animal species using the method Chu et al [ 19 ] successfully applied for the detection of astroviruses in bats in Poland [ 18 ], in wild boars in Slovakia [ 29 ], and in different wild animals in Italy [ 33 ]. Although astroviruses were most frequently detected in rat samples, with a prevalence of 33.3%, the number of samples tested was only nine due to the low number of rat samples submitted during rabies surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggest that the astrovirus detected in a wild boar (AstV_200_2021_wb_POL) was probably transmitted across species via feed from a wild bird or poultry to a wild boar like the previously suggested interspecies transmission events of bat astroviruses via food to wild boars [ 29 ]. The canine astroviruses detected in red foxes in Poland represent the first report of astrovirus detection in foxes in Poland and the fourth report in the world following a study conducted in the Netherlands, Australia, and Italy [ 31 , 33 ]. In the Netherlands and Australia, astroviruses were detected using a metagenomics approach, whereas in Italy a broad range of primers designed by Chu et al [ 19 ] were applied, leading to the detection of AstVs in 5 out of 12 tested samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation